(untitled) (Physical Education, Health and Social Sciences, 2026)
This study investigates the sociolinguistic aspects of language strategy,with a specific emphasis on the psychological impacts of majority languages on self respect. Language framework, frequently presented as an impartial instrument of administration, holds significant societal and psychological outcoms, forming both communal and individual sense of belonging. Based on sociolinguistic theory and psychological research, the paper investigates how hegemonic language beliefs can undermine language of lesswidely spoken language, leading to erode self-esteem,culture estrangement and role of conflicts. By evaluating research cases from multilanguage communities, this article focuses on how language rankings provide an assimilated linguistic disparity and identity construction.The results emphasize the urgent need for comprehensive and diverse language strategies that acknowledge linguistics variety while assistingi ndividual’s emotional well-being. Finally,this study claims that inclusive language strategy is not just a societal imperative but also a cognitive requirement.